2023
DOI: 10.3390/plants12040775
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis Reveals the Metabolic Diversity of Wild and Cultivated Stellaria Radix (Stellaria dichotoma L. var. lanceolata Bge.)

Abstract: Stellaria Radix, called Yinchaihu in Chinese, is a traditional Chinese medicine, which is obtained from the dried roots of Stellaria dichotoma L. var. lanceolata Bge. Cultivated yinchaihu (YCH) has become a main source of production to alleviate the shortage of wild plant resources, but it is not clear whether the metabolites of YCH change with the mode of production. In this study, the contents of methanol extracts, total sterols and total flavonoids in wild and cultivated YCH are compared. The metabolites we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…This study sheds light on the intriguing impact of irrigation on the secondary metabolite contents of Calotropis flowers across different regions within the same Agro-Climatic Zone. The results of our study aligns with the reported literature that cultivated crops have lower levels of active constituents (Ku et al, 2020;Li et al, 2023). This also suggests that irrigation practices may influence the biosynthesis or accumulation of sterols and alkaloids in Calotropis flowers, highlighting the potential impact of environmental factors on the secondary metabolite composition.…”
Section: Effect Of Irrigation On Secondary Metabolite Contentssupporting
confidence: 91%
“…This study sheds light on the intriguing impact of irrigation on the secondary metabolite contents of Calotropis flowers across different regions within the same Agro-Climatic Zone. The results of our study aligns with the reported literature that cultivated crops have lower levels of active constituents (Ku et al, 2020;Li et al, 2023). This also suggests that irrigation practices may influence the biosynthesis or accumulation of sterols and alkaloids in Calotropis flowers, highlighting the potential impact of environmental factors on the secondary metabolite composition.…”
Section: Effect Of Irrigation On Secondary Metabolite Contentssupporting
confidence: 91%
“…Zhang et al demonstrated a significant enhancement in leaf tissue density in Stellaria dichotoma under water stress, but the current study found a significant decrease in caper leaf tissue density with 75% FC. The enhancement of leaf tissue density is primarily related to the decreasing size of leaves under water stress 31 . The opposite result of the current study might be due to the different ecological needs of the caper.…”
Section: Discussionmentioning
confidence: 99%
“…The origin and diversity of Aurantii Fructus are closely intertwined and exert a significant impact on its quality. 20 The specific production region and cultivar contribute to the development of indigenous herbs, characterized by consistently high levels of active ingredients and extensive distribution. Huangpi, a traditional cultivar with a long history of cultivation, is widely recognized as an authentic medicinal plant in Hunan Province.…”
Section: Quality Evaluation and Analysis Of Aurantii Fructus From Dif...mentioning
confidence: 99%